The The Effect of WhatsApp Videos on Pregnant Women's Knowledge About Dental Clinic Visits at Bangkalan, Madura - Futu Hatul Ulumia; Isnanto; Imam Sarwo Edi (International Journal of Advanced Health Science and Technology, 2024)
In everyday life, it is very important to maintain health, one of which is regarding dental and oral health. The problem in this research is the influence of Whatsapp videos on pregnant women's knowledge about visits to the dental clinic at the Kwanyar Health Center, Bangkalan Regency, Madura. The aim of the research was to determine the effect of Whatsapp videos on pregnant women's knowledge about visiting the dental clinic at the Kwanyar Health Center, Bangkalan Regency, Madura. The research method is this research approach is a Quantitative approach, the research method used is the Quasi Experimental method with a Pretest-Posttest Control Group Design research design, the research population is pregnant women in the working area of ​​the Kwanyar Health Center, Bangkalan Regency, Madura. The sample was taken in the form of accidental sampling, namely pregnant women who visited the Kwanyar Health Center Dental Clinic, totaling 30 respondents within a period of one week. Data collection uses a questionnaire via Google Forms. Meanwhile, the data analysis technique is in the form of the Wilcoxon Statistical Test. Research results based on the Wilcoxon Statistical Test showed a ρ value (0.01) < 0.05, it can be concluded that there is an influence of the use of WhatsApp videos on pregnant women's knowledge about visits to the Dental Clinic at the Kwanyar Health Center, Bangkalan Regency, Madura.